Offer of fruits and vegetables in educational institutions of a municipality of the Colombian Caribbean - Vargas-Moranth, Rusvelt Franklin; Alcocer-Olaciregui, Adalgisa Esther; Bilbao-Ramírez, Jorge; Ospino-Gutiérrez, Jesús (Universidad y Salud, 2018)
Introduction: In response to the growing problem of childhood obesity, progress has been made in Colombia in the legislative framework; for instance, the law 1355 of 2009, which indicates that educational institutions should offer fruits and vegetables to school children. Objective: To describe the application of the law 1355 of 2009 facing the supply of fruits and vegetables in educational institutions in the municipality of Soledad, Atlántico. Materials and methods: A descriptive, transversal study was made. Twelve coordinators and six directors were surveyed through a structured form, and a direct observation was made of the availability of fruits and vegetables in the school stores, contrasting both aspects. Results: 8/18 respondents said they know law 1355; 11/18 indicated that there is a leader in their school to lead programs related to healthy eating, which have been advanced in 50% of the institutions; 15/18 (83.3%) responded that there is availability of fruits and vegetables in school stores, but this was only evident in one of the 18 institutions (5.6%). Conclusion: The availability of fruits and vegetables in school stores should be improved as well as the empowerment of managers, teachers, parents and students in order to reduce obesity numbers.